Застосування технологій парогазових енергетичних установок з внутрішньоцикловою газифікацією твердого та рідинного видів палива у світовій енергетиці та перспективи їх впровадження в Україні - Dudnyk О.М.; Dunaevskaya N.I.; Sokolovska I.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
The main parameters of combined-cycle power plants with the integrated gasification of coal (CCPP with IGC) and other solid as well as liquid fuels are considered, and the world experience in application of gasification technologies for combined-cycle power plants in various countries of the world is analyzed. The basic characteristics of CCPP with IGC with and without CO2 capture and storage are shown. At the CCPP with IGC, in addition to electricity production with high efficiency, a series of valuable chemical products (sulfuric acid, hydrogen, ammonia, sulfur, gypsum, etc.) is obtained, which significantly increases the efficiency of these power plants.The prospects for introduction of CCPP with IGC in Ukraine are determined. For gasification in Ukraine, it is possible to use bituminous coal from the Lviv-Volyn deposit, brown coal from the Zhytomyr, Kirovohrad and other regions of Ukraine, as well as petroleum coke, a by-product of the fabrication of liquid substances at the refineries of Ukraine. The choice of an efficient gasification technology depends on the properties of selected solid or liquid fuels. The possibility of using the primary infrastructure of Ukrainian refineries, which are currently stopped, for the construction of CCPP with applying CO2 to increase the extraction of oil and gas from impoverished wells in the west of Ukraine is shown.